KEKHASAN BUNYI BAHASA DAN BENTUK KATA ARKAIS DI DALAM SERAT CIPTAN SABEN ESUK KARYA R. M PARTAWIRAYA DAN R. PRAWIRAHARJA - Bima Aria Teja; Sumarlam Sumarlam; Soediro Satoto (PRASASTI: Journal of Linguistics, 2017)
In terms of beauty or aesthetic aspect which contained in the choice of words of a poet, is an actualization of ideas  or concepts  that attracted of  readers.  Script is a literary work originating from the thinking process of each local poet to actualize his or her ideas and concepts. In relation with the contents packed with the beauty of language use, this research focuses its studies on the Javanese script with piwulang (doctrine) category, namely: Sêrat Ciptan Sabên Esuk. The objectives of this research are to explain: (1) the peculiarity of language sounds aspects, (2) the peculiarity of the utilization of archaic forms. This research used the descriptive qualitative method. The sources of the data were the transliterated script of Sêrat Ciptan Sabên Esuk by Teja in 2014 and its original one. The data included assonance, alliteration, and repetition; the use of archaic forms. The data of research were collected through listening and recording techniques and analyzed by extralingual similirity method. The result of research shows that in the script of Sêrat Ciptan Sabên Esuk, which is in the prose form, are found the use of  assonances, and archaic forms which generally found in poetry (javanese song).  Keywords: Sêrat Ciptan Sabên Esuk, the peculiarity of language sounds, and archaic forms of words.